1970
DOI: 10.3126/njst.v11i0.4134
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Sustainable Conservation of <i>Swertia chirayita</i> (Roxb. ex Fleming) h. Karst in Nepal

Abstract: Swertia chirayita (Roxb. ex Fleming) H. Karst is one of the most important high-value medicinal plants of Nepal prized for its anti-diabetic, antimalarial, hepato-protective and anti-inflammatory properties. It is widely used as an important ingredient in medicinal preparations in Ayurveda, Unnani, Siddha, Tibetan and Chinese traditional medicine. Nepal is one of the main exporters of this important plant and the most significant importers are India and China. The large scale export of this plant has made it v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… 327 *Swertia chirayita (Roxb. ex Fleming) Karsten Herb Gentianaceae Tikta (Km, Sh, Wi); Sungkhinwa (Li); Chiraito, Chiraita, Tite (Np); Khalu (Nw); Kuple (Ri); Kirattikta (Sn); Timda (Tm); Gya-Tig, Tigta (Tb) 1200-3000 Plant and seeds: Plant infusion and crushed seeds considered most effective in treating fever (Taplejung: [ 81 ]; KL Nepal: [ 83 , 103 ]; Ilam: [ 73 , 76 ]), asthma, cold, and cough (Darjeeling: [ 80 ]; Taplejung: [ 81 , 87 ]; KL Nepal: [ 83 , 103 ]; Sikkim: [ 11 ]; Ilam: [ 73 , 76 ]). Whole plant: Used as medicine (KL Bhutan: [ 71 ]).…”
Section: Methodsmentioning
confidence: 99%
“… 327 *Swertia chirayita (Roxb. ex Fleming) Karsten Herb Gentianaceae Tikta (Km, Sh, Wi); Sungkhinwa (Li); Chiraito, Chiraita, Tite (Np); Khalu (Nw); Kuple (Ri); Kirattikta (Sn); Timda (Tm); Gya-Tig, Tigta (Tb) 1200-3000 Plant and seeds: Plant infusion and crushed seeds considered most effective in treating fever (Taplejung: [ 81 ]; KL Nepal: [ 83 , 103 ]; Ilam: [ 73 , 76 ]), asthma, cold, and cough (Darjeeling: [ 80 ]; Taplejung: [ 81 , 87 ]; KL Nepal: [ 83 , 103 ]; Sikkim: [ 11 ]; Ilam: [ 73 , 76 ]). Whole plant: Used as medicine (KL Bhutan: [ 71 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Almost Swertia species (including Swertia lawii ) are rich source of oleanolic acid and ursolic acid, two pharmacologically important compounds [7] , [8] , [9] . S. lawii is an important medicinal herb which is used as adulterant and also as substitute to S. chirayita [10] , [11] , [12] . Several xanthone compounds were isolated from various organs of S. lawii and it was found that it is rich source of erythrocentaurin, an important bioactive compound [10] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and severity of the disease in the area may be due to the presence of shade of tree, shrubs and unwanted associated weeds in the fields. These conditions reduce light intensity and increase in humidity that favors the distribution of the pathogen (Gashaw et al, 2014) (Phoboo & Jha, 2010;Bhatt et al, 2007;Sharma et al, 2011).These associated species favour the growth of pathogens providing shade to the cultivated plant of the area. Fungi are known as emerging destructive pathogens of agriculturally important crops, causing the loss of billions of euros every year (Gomes et al, 2021).…”
Section: Resultsmentioning
confidence: 99%